2020
DOI: 10.3390/electronics9030408
|View full text |Cite
|
Sign up to set email alerts
|

Incentive and Penalty Mechanism for Power Allocation in Cooperative D2D-Cellular Transmissions

Abstract: In cellular communication systems, the introduction of device-to-device (D2D) communications provides a reasonable solution to facilitate high data rate services in short-range communication. However, it faces a challenging issue of interference management, where the cross-tier interference from D2D users to licensed cellular users (CUs) degrades their quality-of-service (QoS) requirements. D2D communications can also assist in offloading some nearby CUs to enhance the cellular operator's benefit. To encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The experimental results show a win-win situation. A detailed study of game theory for the 5G network may be found in [26]. Offloading through Wi-Fi technology has gained more popularity due to the built-in capability of smartphones.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results show a win-win situation. A detailed study of game theory for the 5G network may be found in [26]. Offloading through Wi-Fi technology has gained more popularity due to the built-in capability of smartphones.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [21] analyzed three signal demodulation schemes in the uplink based on the outage probability, trying to reduce the influence of D2D users on the base station through mode selection, and at the same time derive the interference restriction area in the [22] to prevent Adjacent users reuse the same cellular resources. The authors in [23] studied and analyzed the applicability of the LTE power control scheme in D2D systems, and concluded that the hybrid network interference problem must be a combination of power control, mode selection, link adaptation and other technologies. The authors in [24] optimized the transmission power of different users based on system energy efficiency modeling, using sub-optimal algorithms of upper and lower bounds.…”
Section: Introductionmentioning
confidence: 99%